Awareness of environmental protection amongst Muslims in Ampara District - Saujan, Iqbal; Razick, Ahamed Sarjoon (Penerbit Universiti Kebangsaan Malaysia, 2021)
Environmental protection is the practice of protecting the environment for the betterment of humans and the natural environment with the assistance of individuals, organizations or states. The main objective of this research is to evaluate the level of environmental awareness among Muslims in Ampara District of Sri Lanka. Primary data were collected by administering a questionnaire to 384 selected participants from the total Muslim population residing in Ampara District. All the data from received questionnaires were analyzed through a descriptive method using SPSS software. In addition, research articles, web publications, books, journals, and Islamic sources such as the Qur’an, Sunnah, and the opinions of contemporary Islamic scholars were used as secondary sources in this study. According to results, the model shows that the informants were well aware of environmental protection, and 96.3% of them eagerly acknowledged the relationship between Islam and environmental protection. About 94% of them accepted the link between environmental protection and physical health, and were concerned with protecting the environment in which they live. Moreover, approximately 33% of them had the habit of keeping their environment clean on a daily basis. In summary, awareness of environmental protection in the sample is at a healthy level, and this knowledge is influenced by their religious guidelines. However, despite the sufficient awareness of participants in protecting the environment, they did not show much interest in practicing it. This research will help strengthen environmental protection by voluntary organizations and assist policymakers in the country to take the necessary measures. The study could serve as a starting point for future research to guide the general public on environmental protection.